New Law Threatens Free Speech, Trans Rights - Human Rights Watch (Human Rights Watch, 2025)
A law enacted in Peru purports to combat sexual violence against children and adolescents, but instead undermines freedom of expression and access to information, and discriminates against transgender people, Human Rights Watch said today. The law’s vague and overly broad provisions could also be used to suppress expressions of identity, artistic content, and educational materials while failing to effectively address pervasive sexual violence against children and adolescents in the country.